Impulsionadores e inibidores para a utilização do design thinking no PDP de micro, pequenas e médias indústrias - Redante, Roberta Cristina (2018)
Design thinking is an iterative approach that contrasts with the traditional new product development process (NPD), which is considered a linear process. This research’s objective is to broaden the knowledge on the concepts and processes associated to design thinking, to investigate the inhibitors and influencers for their use as an approach to the new product development process. As for the method, initially was performed a systematic literature review, which allowed the mapping and analysis of 54 published articles in 12 journals indexed in the “Science Direct” and “Web of Science” databases. In addition, a quantitative descriptive research was carried out with micro, small and medium industries of the furniture sector in the region of serra gaúcha. Data were analyzed by frequency analysis and by cluster analysis. As for results, the main drivers for the implementation of the design thinking are a possibility to improve the results of innovation and testing as solutions before launching to market. Moreover, among the inhibitors listed, none of them were considered relevant. Also, it is presented as a result the relation directly proportional between company size, NPD methods and multidisciplinary teams. Finally, it is also worth highlighting that design thinking can provide a new look to the NPD, since it is based on user engagement and multifunctional teams.